Análise do processo de integração ao mundo do trabalho dos alunos egressos de curso técnico, sob a perspectiva de valores pessoais construídos a partir da realidade percebida - Pereira, Ana Ioneide de Souza Bandeira (2014)
Professional education in Brazil has been marked throughout its historical trajectory by the stigma of exclusion and of social segregation, the end goal of which was summed up as only formation for manual labor. Currently, given the new demands of the work world, professional education has increasingly taken on a role of relevant importance, as it proposes, within the formation of the young people, to transmit not only technical knowledge, but, above all, to form the human being with a base in personal values, ethics and morals, as a way of guaranteeing the integral formation of the human being, from the perspective of constructing a more just, equalitarian society whose principles of fraternity, justice, loyalty and love toward the neighbor are determinant in the relations between human beings and of these with God. In this perspective, this paper is an analysis of the process of integration of outgoing students of the technical programs into the work world, from the perspective of the formation of personal values constructed through the formation obtained in the Instituto Federal de Educação, Ciência e Tecnologia do Ceará [Federal Institution of Education, Science and Technology of Ceará]- campus of Cedro. This analysis constitutes the general goal of this investigation the specific goals of which are: identify the historical factors related to professional education in Brazil; comprehend the importance of personal values and of ethics in the process of professional formation; analyze the relation of the technical formation, from the perspective of the formation of personal values, morals and ethics, to the demands of the work world. In the first chapter information about the historical trajectory of professional education in Brazil is presented, beginning with the Colonial period to the current days. In the second chapter, information is referenced which is pertinent to the role of education as promoter of personal values, morals and ethics which are indispensable for the process of formation of the human being and are understood as elements of extreme importance in the process of integration of outgoing students from the technical program into the work world. In the third chapter, we deal with the procedures and methods which provided support for the proposed study, and, finally, in the fourth chapter, we proceed with an analysis about the technical formation obtained through professional education allied to the formation of personal values, morals and ethics, seeking to understand up to what point did this formation actually take place and in what way did it impact the life of the young people seeking opportunities for work and consequently better living conditions. The study was supported by a pertinent theoretical referential of the theme, as well as by statements from the outgoing students of the technical program in electro-technology, which provided the foundation for the arguments which reference the Instituto Federal de Educação, Ciência e Tecnologia do Ceará - campus de Cedro, as an institution which promotes efficient professional education to not only form technicians but to also prepare human beings with an adequate ethical posture, exemplary behavior and with life stories which were changed due to the opportunity of being technicians in electrotechnology.